2021
DOI: 10.1002/nvsm.1725
|View full text |Cite
|
Sign up to set email alerts
|

Transparency of nonprofit organizations: An integrative framework and research agenda

Abstract: Over the past 20 years, as the study of transparency has evolved into a burgeoning multidisciplinary field, nonprofit scholars have developed an impressive body of research on the antecedents and outcomes of the transparency of nonprofit organizations (NPOs). From both theoretical and practical purposes, it is necessary to develop an overall picture of such antecedents and outcomes, to allow scholars and NPOs to understand why, when, and how transparency should be implemented. Current studies provide a fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…In addition to moral responsibility, researchers also investigated whether sociodemographic factors such as age, length of service, educational background, and political party regeneration were also significant in determining the transparency of financial information disclosure (Dethier et al, 2021;Kendall & Knapp, 2000;Kumlin, 2006;Torres & Pina, 2003). Age is related to the inner maturity and maturity of a person's mindset.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to moral responsibility, researchers also investigated whether sociodemographic factors such as age, length of service, educational background, and political party regeneration were also significant in determining the transparency of financial information disclosure (Dethier et al, 2021;Kendall & Knapp, 2000;Kumlin, 2006;Torres & Pina, 2003). Age is related to the inner maturity and maturity of a person's mindset.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid growth of the nonprofit sector, concerns about transparency and accountability of nonprofit organizations have also increased (Dethier et al, 2021; Moreno‐Albarracín et al, 2020). Nonprofit organizations must earn the public's trust in order to acquire necessary resources and sustain themselves in the midst of stiff competition in global philanthropy.…”
Section: Introductionmentioning
confidence: 99%
“…The increased importance of nonprofit transparency has also resulted in growing research interests in identifying the determinants and antecedents of nonprofit transparency, and existing research has found that factors such as stronger governance and professionalized staff contribute to transparency (Dethier et al, 2021; Harris & Neely, 2021). Among others, the ethical leadership literature suggests that organizational transparency is closely related to leader gender, reporting that organizations led by women exhibit higher levels of transparency than those led by men (Glass & Cook, 2018; Ingersoll et al, 2019; Zou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to goal setting, NPOs often have to juggle what appear to be conflicting objectives set by management needs. Communication goals related to transparency, for instance, have been considered problematic by scholars that look to NPO needs of balancing audiences' skepticism (Dethier et al, 2021). In regard to the public, nonprofit communication operates on a multilayered level, considering a diverse group of stakeholders, including donors, volunteers, minority groups, activist groups, regulatory bodies, other NPOs, and the like.…”
Section: Introducing the Fieldmentioning
confidence: 99%